Restoring sights: a story of six eye care projects in Bangladesh - Chowdhury, A. Muahtaque R.; Mustafa, Shams (© BRAC, 2016)
1. Introduction 2. Operation eyesight universal 3. Problem of blindness and programmes in Bangladesh 4. Evaluation methodology and limitations 5. Evaluation results